Dye Uptake and Thermal Behavior of Fibre Grade PET Containing Boltorn H40 as a Nanomaterial (Journal of Fiber Bioengineering and Informatics, 2012)
In this work, various loads of nanomaterials and aliphatic dendritic polymerswere mixed with fibre gradePET (Polyethylene terephthalate) to study its dye ability, thermal and thermal-mechanical properties.A twin screw extruder equipped with sheet (profile) die was used for mixing the compounds. Thermalbehaviour of the neat PET and the compounded sheet samples were studied using differential scanningcalorimeter and dynamic mechanical thermal analysis. It was observed that the T_g of samples decreasedgradually by increasing the load of Boltorn H40 as a nanomaterial additive while the T_m remained almostthe same. The difference between the glass transition temperature for neat PET and the compoundedsample including 3% additive was about seven degrees. In spite of the decline in T_g, the moduli ofsamples containing additive increased as revealed by DMTA analysis. The presence of this dendriticpolymer in compounded PET acted as a cross linking or antiplastisizing agent and made the fibre gradePET compounds more compact than pure PET. So the disperse dye molecules neither were able to staybetween the molecules of compounded PET nor were able to trap between the dendritic branches.